Effects of a sit-to-stand plus heel raise exercise program on predicted maximal oxygen consumption in sedentary adolescents - Januariska Herma Widhianti; Yudith Dian Prawitri; Nur Sulastri; Atika (Physical Therapy Journal of Indonesia, 2026)
Background: Sedentary behaviour in adolescents is associated with lower cardiorespiratory fitness and higher cardiometabolic risk. Simple functional exercises may represent a practical and accessible way of improving aerobic fitness in school settings. This study aimed to examine the effects of a sit-to-stand plus heel-raise (STS-HR) exercise program on maximal oxygen consumption (VO₂max) in inactive male adolescents. Methods: This single-blind randomized controlled trial was conducted in a high school in Surabaya, Indonesia from July to November 2025. Inactive males aged 15-17 years were randomly assigned to either a control group that did not participate in organized exercise or an intervention group that underwent 8-week supervised STS-HR program three times per week. Predicted VO₂max was assessed before and after the intervention using the Chester Step Test by blinded assessors. Results: Thirty-seven of 39 randomized participants completed the trial. The STS-HR group had a significant increase in predicted VO₂max (36.14 ± 8.53 to 46.52 ± 7.90 mL·kg-1·min-1; p < 0.001) whereas the control group did not (41.48 ± 8.24 to 41.33 ± 9.23 mL·kg-1·min-1; p = 0.911). The between-group difference in change in VO₂max was 10.53 mL·kg-1·min-1 (95% confidence interval: 6.89 to 14.17; p < 0.001). No adverse events, exercise-related discomfort, or injuries were reported during the intervention. Conclusion: An 8-week supervised STS-HR program led to a significant increase in predicted VO₂max in inactive male adolescents. These results provide evidence that simple functional exercises may be an effective and low-cost feasible school-based strategy to improve cardiorespiratory fitness in inactive youth.